مشكلة تعاطي المخدرات داخل المؤسسات التعليمية بمدينة باتنة ودورها في الوقاية منها. دراسة ميدانية لمدينة باتنة (ثانوية حي عيون العصافير نموذجا) - مشنان, فوزي; مطمر, محمدالعيد (جامعة الوادي - University of Eloued, 2021)
تهدف الدراسة إلى التعرض إلى أخطر الظواهر التي يعاني منها مجتمعنا الباتني خاصة داخل المؤسسات التعليمية، ألا وهي ظاهرة الإدمان، و التي نعرضها من خلال التعرض لمفهوم هذه الظاهرة، وتحديد أسبابها و خصائصها و أبعادها، إضافة إلى إبرازأهم الجوانب التي تمس الظاهرة وتثيرها خاصة الإجتماعية منها ، دون إهمال الجوانب الأخرى لها، مع إبرازدور هذه المؤسسات في الوقاية من هذه الظاهرة، وسبل معالجتها القضاء عليها أسريا ومجتمعيا. وقد توصلنا في النهاية إلى نتيجة هامة تمثلت في أن الجانب الإجتماعي هو السائد و الأساسي في حدوث الظاهرة وانتشارها في مجال الدراسة. The study aims at exposure to the most dangerous phenomena encountered by Alebattna our society in particular in educational institutions, namely the phenomenon of dependence, and show us through exposure to the concept of this phenomenon , and to determine their causes and characteristics and dimensions, as well as the Abrazohm aspects that affect the social and high private phenomenon, without neglecting other aspects of sound, with Abrazdor these institutions in the prevention of this phenomenon, and the means to deal with it eliminated a family and a community. We reached at the end of an important result was that the social aspect prevails in the primary and the appearance and spread of this phenomenon in the field of study
The problem of drug abuse within educational institutions in Batna and its role in prevention . A field study for the city of Batna (secondary school district, Ayoun Al Asafir as a model
مقال
Keywords: المخدرات ، التعاطي ، الإدمان، المشكلة الاجتماعية للإدمان على المخدرات.; drugs ; Negotiation ; Aladman; the social problem of drug addiction.